The redox signal: A physiological perspective. Issue 1 (3rd September 2021) - Margaritelis, Nikos V.; Chatzinikolaou, Panagiotis N.; Chatzinikolaou, Alexandros N.; Paschalis, Vassilis; Theodorou, Anastasios A.; Vrabas, Ioannis S.; Kyparos, Antonios; Nikolaidis, Michalis G.
Abstract: A signal in biology is any kind of coded message sent from one place in an organism to another place. Biology is rich in claims that reactive oxygen and nitrogen species transmit signals. Therefore, we define a "redox signal as an increase/decrease in the level of reactive species". First, as in most biology disciplines, to analyze a redox signal you need first to deconstruct it. The essential components that constitute a redox signal and should be characterized are: (i) the reactivity of the specific reactive species, (ii) the magnitude of change, (iii) the temporal pattern of change, and (iv) the antioxidant condition. Second, to be able to translate the physiological fate of a redox signal you need to apply novel and bioplausible methodological strategies. Important considerations that should be taken into account when designing an experiment is to (i) assure that redox and physiological measurements are at the same or similar level of biological organization and (ii) focus on molecules that are at the highest level of the redox hierarchy. Third, to reconstruct the redox signal and make sense of the chaotic nature of redox processes, it is essential to apply mathematical and computational modeling. The aim of the present study was to collectively present, for the first time, those elements that essentially affect the redox signal as well as to emphasize that the deconstructing, decoding and reconstructing of a redox signal should be acknowledged as central to design better studies and to advance our understanding on its physiological effects.